POLA KERJASAMA GURU DAN ORANG TUA DALAM MENJAGA MUTU PENDIDIKAN MELALUI PROSES PEMBELAJARAN DARING SEBAGAI UPAYA STUDY FROM HOME (SFH)PADA MASA PANDEMI DI SDN 1 JANAPRIA - Munawir Gazali (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
As a result of the Covid19 virus impact that has not subsided, the learning process will continue to be carried out from each home (study from home). The problems raised in this study are how the pattern of cooperation between teachers and parents in maintaining the quality of education during a pandemic and how is the form of cooperation between teachers and parents in maintaining the quality of education during the pandemic. Starting from the formulation of the problem, the purpose of this research is to determine the pattern of cooperation between teachers and parents in maintaining the quality of education during the pandemic and to know the form of cooperation between teachers and parents in maintaining the quality of education during the pandemic. This research used a qualitative descriptive approach. The research subjects was SDN 1 Janapria. Technique of data collection of this research were used interview, observation and documentation. To test the credibility of the data in this research the researcher used triangulation techniques. The sources of information were classroom teachers, head master, student's parents, and students. The results showed that the pattern of cooperation between teachers and parents in maintaining the quality of education during the pandemic was by establishing communication with student's parents and facilitating online learning needs. As for the form of collaboration between teachers and parents in maintaining the quality of education during the pandemic, namely parents must maintain and ensure children to implement the clean and healthy life, accompanying children in the online learning process and doing school assignments, guiding and motivating children, establishing communication Intense with Children, Becoming a Role Model for Children, Making Variations and Innovating Activities at Home.